The Influence of Motivation, Ability and Experience on Employee Performance - Yana Fajriah; Nurhasni Muis; Risma Yanti; Ardiansyah Halim (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
This study aims to analyze and examine the effect of motivation, ability, and experience on employee performance in the district office of the Gowa Regency. Data collection in our study was carried out by distributing questionnaires to 96 employees. The research data were analyzed in several stages using multiple linear regression analysis models and using SPSS tools. This study indicates that all variables, namely the motivational factor of experience ability, have a positive and significant influence either simultaneously or partially. The work motivation factor has a significant and most dominant influence on employee performance at the Gowa District office. This study suggests that the government of the district office of Gowa Regency can pay more attention to factors that can encourage work performance, such as providing motivation and providing opportunities for further studies that can further stimulate employees to work further.